Exploring Factors Linked to Weight Status in Salvadoran Infants. (June 2021) - Kiraly, Carmen M.; Turk, Melanie T.; Kalarchian, Melissa A.; Shaffer, Cheryl
Introduction: Potential risk factors of infant overweight/obesity in Salvadoran mother–infant dyads ( N = 88) at routine 9- to 12-month wellbaby visits were examined in a correlational study at two pediatric offices on Long Island, New York. Method: Maternal factors and infant feeding practices in the first 5 months were self-reported; infant birth weight, current weight/recumbent length were obtained. Bivariate logistic regression measured the relationship of the variables with infant weight status >85th percentile weight-for-length (WFL) for sex. Results: The majority of mothers were born in El Salvador, with a mean age of 28.5 years ( SD = 5.9); 43% of infants had WFL >85th percentile. Infant birth weight was significantly associated with WFL >85th percentile, p = .0007. After controlling for maternal age, insurance type, education, and marital status, no significant associations with infant WFL >85th percentile were found. Feeding practices during infants' first 5 months, mothers' pre-pregnancy weight, pregnancy weight gain, and history of gestational diabetes mellitus, were not associated with infant weight status. Conclusion: This was the first study to examine infant weight status in Salvadorans. Future studies should objectively measure infant feeding practices and other potential factors among Salvadoran mother infant dyads, since nearly half of the infants had WFL >85th percentile.